Early changes in apoplast composition associated with defence and disease in interactions between Phaseolus vulgaris and the halo blight pathogen Pseudomonas syringae Pv. phaseolicola. (25th July 2016) - O'Leary, Brendan M.; Neale, Helen C.; Geilfus, Christoph‐Martin; Jackson, Robert W.; Arnold, Dawn L.; Preston, Gail M.
Abstract: The apoplast is the arena in which endophytic pathogens such as Pseudomonas syringae grow and interact with plant cells. Using metabolomic and ion analysis techniques, this study shows how the composition of Phaseolus vulgaris leaf apoplastic fluid changes during the first six hours of compatible and incompatible interactions with two strains of P. syringae pv. phaseolicola ( Pph ) that differ in the presence of the genomic island PPHGI‐1. Leaf inoculation with the avirulent island‐carrying strain Pph 1302A elicited effector‐triggered immunity (ETI) and resulted in specific changes in apoplast composition, including increases in conductivity, pH, citrate, γ‐aminobutyrate (GABA) and K +, that are linked to the onset of plant defence responses. Other apoplastic changes, including increases in Ca 2+, Fe 2/3+ Mg 2+, sucrose, β‐cyanoalanine and several amino acids, occurred to a relatively similar extent in interactions with both Pph 1302A and the virulent, island‐less strain Pph RJ3. Metabolic footprinting experiments established that Pph preferentially metabolizes malate, glucose and glutamate, but excludes certain other abundant apoplastic metabolites, including citrate and GABA, until preferred metabolites are depleted. These results demonstrate that Pph is well‐adapted to the leaf apoplast metabolic environment and that loss of PPHGI‐1 enables Pph to avoid changes in apoplast composition linked to plant defences. Abstract : The apoplastic compartment is the arena in which endophytic pathogens such as Pseudomonas syringae grow and interact with plant cells. Controlling the composition of the apoplast during plant–pathogen interactions could underlie evolutionary strategies for survival of both the host plant and invading bacteria. Here we combine an apoplast extraction method with metabolomic and ion analyses techniques to describe the composition of the apoplast of Phaseolus vulgaris leaves, and to determine changes in apoplast composition associated with resistant and susceptible interactions with the bacterial pathogen P. syringae pv. phaseolicola . We demonstrate that the apoplast is replete with nutrients that can be used to support pathogen growth, and identify certain ions and metabolites that increases dramatically in the apoplast of plants expressing effector‐triggered immunity